Білінгвізм як ознака функціонування сучасного полікультурного суспільства - Драпалюк, Галина; Олексів, Галина; Шийка, Юлія (Видавництво Львівської політехніки, 2017)
The article deals with the analysis of the scientific-pedagogical literature and concerns the problems of bilingualism. Bilingualism is viewed as ability of a person to use two languages to fulfill communicative needs; as recognition and functioning of two languages within one state; as social phenomemon and individual characteristics of a person. Economic, psychologic, educational, social and cultural factors were shown which caused popularization and spreading of bilingualism. Much of the current literature distinguishes various types of bilingualism: elective, circumstantial, school and cultural bilingualism which have different features and causes of appearance. The key differences betweenmain types of bilingualism were highlighted.
Keywords: білінгвізм; шкільний білінгвізм; культурний білінгвізм; державна мова; іноземна мова